The Status and Prescription Patterns of Opioid Utilization in a Large Comprehensive Teaching Hospital in China According to the Anatomical Therapeutic Chemical Classification/Defined Daily Dose Methodology - Fang, Ting; Zhang, Xiaojie; Hao, Wei; Deng, Qijian (Frontiers in Psychiatry, 2022)
Background Few studies have analyzed opioid consumption and the average daily dose and duration for different patients in hospital settings in China. The aim of this study was to measure the status of and trends in prescribed opioids and the prescribing patterns at the Second Xiangya Hospital. Methods The data were obtained from the prescribed medicine database of the inpatient department. We included patients who were >18 years old and received any level of opioid analgesic between 2012 and 2017. The international Anatomical Therapeutic Chemical Classification/Defined Daily Dose (ATC/DDD) methodology was used to standardize the consumption rates. All opioid units were converted into morphine equivalents (MEs) to analyze the specific opioid usage. Results The consumption of prescribed opioids increased from 3.16 to 3.74 DDD/100 bed-days (+18.3%) from 2012 to 2017. Both cancer and noncancer patients had similar administration routes and median daily dosages in MEs, but cancer patients had longer treatment durations (median: 5 days vs. 1 day, respectively). The median average daily dose and treatment duration for all patients were 15 MEs/day and 2 days, respectively, for oral administration, 100 MEs/day and 1 day for parenteral administration, and 47.14 MEs/day and 5 days for both oral and parenteral administration. Conclusion Although there was a tendency toward an increase in opioid consumption, the overall level of consumption in the Second Xiangya Hospital remained relatively low. Thus, it is urgently necessary to increase the availability of opioids and alter prescription habits for them in order adopt the current concept of pain management developed by the World Health Organization (WHO).